Index based agricultural water availability in Rechna Doab, Pakistan: development of an agricultural water availability index and its application under climate change in Rechna Doab, Pakistan [Thesis]. - Ahmad, Waqas (Lambert Academic Publishing, 2012)
Climate change will affect the hydrologic cycle and thus it will have significant implications on the regional scale water availability from a number of sources. An index based assessment of the present and future water availability was carried out in this research. The Agricultural Water Availability Index was developed for Rehna doab, Pakistan. The study area was divided in four irrigation circles and further in to a grid of 1000 x 1000 m. The present and future water availability from canal diversions, rainfall, groundwater with its quality consideration and stored soil moisture was assessed. The results revealed that water availability is higher in the eastern parts of the study area and following a general trend it reduces towards the west. The mean index value for the present scenario in the study area was determined as 0.30. It was further investigated that water availability is varying throughout the year. In UCC irrigation circle the Agricultural Water Availability Index varies from -0.17 to 0.28 the minimum value was observed in December and the maximum in August. The corresponding index values for LCC-East, LCC-West and Haveli circle were from -0.16 to 0.15, -0.15 to 0.15 and -0.18 to 0.07 respectively. The current cropping intensities in the four irrigation circles were 152, 113, 115 and 114 percent respectively. An increase rainfall distribution and canal diversions were bserved in all future scenarios. Moreover the future rainfall was observed to have more fluctuation throughout the year. In comparison with the present situation it was noted that under future scenarios the spring season water availability would increase. The overall index value for UCC, LCC-East, LCC West and Haveli circle varies from - 0.21 to 0.65, -0.23 to 0.44, -0.25 to 0.41 and -0.27 to 0.29 respectively. This shows that the present trend of water availability across the circles is also observed in the future scenarios. Moreover the minimum and maximum extremes were observed to be more severe with August being the wettest and November being the driest months. More fluctuation in water availability was observed in Haveli circle, which means that comparatively more arid area are more vulnerable to climate change. This was evident from the spring water availability in Haveli circle where the range if index was from -0.02 to 0.14 for A2T2 and B2T2 scenarios respectively. The extreme water shortages for future scenarios in the months of May and November pose a serious threat to the major crop in the study area. Based on the results it was found that there was a shortage of water at the critical time of sowing of wheat, cotton and sweet pea therefore suitable climate change adaptation options were forwarded to cope with these shortages. It was suggested to adapt water conservation technologies during the sowing period of these crops as it saves time and conserve stored soil moisture for the development of crops. The overall results of this study can be used for making better surface water allocation in the future on the basis of knowing water availability on a spatial scale. As an example more surface water from the UCC circle can be transferred to the other areas where groundwater of usable quality is not available.